Determination of Transference Number and Thermodynamic Factor by use of Anion-Exchange Concentration Cells and Concentration Cells. Issue 13 (16th August 2019) - Craig, Nathan; Mullin, Scott A.; Pratt, Russell; Crane, Gabriel B.
Abstract : A method is described for the measurement of lithium ion transference number and thermodynamic factor of a binary electrolyte by the combined use of anion-exchange concentration cell measurements and concentration cell measurements. The measurements were carried out using cells consisting of LiTFSI salt, a poly(ethylene oxide) solvent, a polydiallyldimethylammonium bis(trifluoromethanesulfonyl)imide anion-exchange layer, and lithium foil electrodes. The transference number and thermodynamic factor were fit using expansions suggested by electrolyte theory. The thermodynamic factor was measured to lie within the range 0.3 to 6 at 80°C. The lithium ion transference number was measured to be 0.18 at infinite dilution and decreased with increasing concentration. Under ideal operation, the anion-exchange concentration cell directly measures the difference in the chemical potential of salt at two different concentrations. The accuracy of the approximation of ideal operation was estimated, showing that the method is more accurate as the salt has low partitioning into the anion-exchange layer and as the salt diffusivity in the anion-exchange layer is lower than in the solvent.